DEVELOPING INTERACTIVE LEARNING MEDIA BASED ON ADOBE ANIMATE APPLICATIONS FOR GEOMETRY TRANSFORMATION - Baihaki Baihaki; Soraya Djamilah; Ahmad Lazwardi (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
Some mathematical material will be challenging to understand without learning media, primarily topics that requires visualization, such as geometric transformations. This study aims to describe the process of developing interactive learning media based on the Adobe Animate application of geometry transformation. It also describes the validity and practicality of the developed learning media. This type of research is research and development. The product developed was an interactive learning media application on geometry transformation material created using Adobe Animate. The development model used was the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, collection of materials, manufacture, testing, and distribution. The research found that the interactive learning media developed were fairly valid (80.12%), with a high level of practicality (4.19). Overall, the learning media developed is feasible to be used in the learning process or as a means of independent learning for students of geometry transformation.